The Impact of Broch’s Work on Serbian Dialectology - Milosavljević, Tanja Z.; Savić-Grujić, Ana R. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The speeches of the Prizren-Timok dialect area represent the most thoroughly studied part of the Serbian linguistic environment. They have been examined by numerous Slavic linguists, as well as by scholars of non-Slavic origin, the first of whom was the Norwegian Slavic linguist Olaf Broch, a professor of Slavic languages from Oslo. His monograph on the dialects of the southernmost parts of Serbia, Die Dialekte des südlichsten Serbiens, published in German in Vienna in 1903, paved the way for future intensive and fruitful studies of the southernmost Serbian dialects. On the occasion of the 120th anniversary of its publication, in 2023 the Embassy of the Republic of Serbia in the Kingdom of Norway and the Norwegian Academy of Science and Letters held a celebration to honor the renowned Norwegian Slavic scholar Olaf Broch. The guests of honor included T. Milosavljević, a representative of the SASA Institute for the Serbian Language, who delivered a presentation prepared specifically for this jubilee and co-authored with A. Savić-Grujić. This paper represents a more recent and extended version of that presentation. Based on detailed and numerous analyses of Broch’s monographs carried out by the most influential Serbian dialectologists, as well as on analyses of Broch’s own work on the speeches of the Prizren-Timok dialect area, the authors attempt to reconstruct the scientific and cultural insights that bring these dialects fully into the limelight. Even though later studies of this dialect area have indicated that some of the findings in Die Dialekte des südlichsten Serbiens were not always sufficiently precise, Olaf Broch should be honored, as his scientific endeavors—and the data that informed them—mark the beginning of systematic and detailed study of the speeches of the Prizren-Timok dialects, and, at the same time, the beginning of the history of the scientific study of Serbian dialects.